Test tasks by the system "KROK-2". Rheumatology - Shehovceva, Т. G.; Svistun, S. I.; Dolinnaya, M. A.; Шеховцева, Тамара Григорівна; Свистун, Сергій Іванович; Долінна, Марія Олександрівна (Zaporizhzhya state medical university, 2016)
Practical work of internal diseases for independent preparation to practical studies for students of medical faculty of 6 course and doctors - interns. Practical work is represented as collection of test tasks and clinical tasks with standarts of true answers on rheumatology.